Triple-Negative Breast Cancer And It's Therapeutic Options - C.B.S. DANGI,; A. FIRODIYA, (International Journal of Pharma and Bio Sciences, 2012)
Triple-negative breast cancer (TNBC) is subtype, accounts 15-20% of breast cancers, which does not express estrogen receptor (ER), progesterone receptor (PR) or human epidermal growth factor 2 (HER2). BRCA1 related pathway significantly contributes in the development of TNBC. Premenopausal African-American women are majorly associated and unique molecular features, aggressive behaviors, early pattern of metastatis and poor prognosis are characteristics of it. Eventhough, better results observed through chemotherapy in neoadjuvant, adjuvant and metastatic treatment of TNBC, role of specific chemotherapy agents was not completely understood. Currently different therapeutic agents for TNBC are platinum agents, signaling pathway inhibitors, Poly-(ADP-ribose)-polymerase inhibitors, antiangiogenic agents, microtubule inhibitors, androgen receptor based therapy, histone deacetylase inhibitors and heat shock protein 90 inhibitors. Further molecular insight will optimize therapeutic strategies for TNBC patients.